Facilitation tools to enhance the alignment of scientific technical assistance with agribusinesses and create buy-in among key stakeholders: Communication framework - Peterson, Nathanial (2024)
Effective agribusiness support requires bridging gaps between scientists and companies while addressing two major challenges: scientists’ limited understanding of business realities and the lack of stakeholder alignment within agribusinesses. To improve scientist-company collaboration, we created a mutual interview protocol that fosters efficient, productive discussions and informs future matchmaking. Simultaneously, we developed a communication framework to help companies present scientific insights effectively to key stakeholders, ensuring alignment and securing financial support. These tools aim to improve the adoption of technical assistance, scale CGIAR innovations, and enhance the impact of agribusiness support programs.